Land-Use Planning and Management Strategies for a Sustainable Greater Jabotabek - Mike Douglass (The Institute for Research and Community Services, Institut Teknologi Bandung, 1996)
Land-use strategies for a sustainable Greater Jabotabek focus attention on balancing economic and social requirements with those for maintaining the integrity of the natural environment. Two levels, region